A Note on Lacunary Sequence Spaces of Fractional Difference Operator of Order α,β - Qing-Bo Cai; Sunil K. Sharma; Mohammad Ayman Mursaleen (Journal of Function Spaces)
In the present paper, we defined lacunary sequence spaces of fractional difference operator of order α,β over n-normed spaces via Musielak-Orlicz function M=Ik. Our aim in this paper is to study some topological properties and inclusion relation between the spaces I−NαβA,M,u,θ,Δγ,·,⋯,·0, I−NαβA,M,u,θ,Δγ,·,⋯,·, and I−NαβA,M,u,θ,Δγ,·,⋯,·∞.